Peranan balai penerangan pemuda dalam perjuangan kemerdekaan perjuangan kemerdekaan di padang(AGUSTUS-NOVEMBER 1945 - yunis, Rahma - (Pendidikan Sejarah, 2014)
BPPI is feminist organization group that is start in intermediate feminist condition developing independence. Actioning of BPPI is part of doing some activities in developing independence at Sumatera Barat (Padang). Ismail is a figure of feminist in independence Indonesia and revolusioner goverment group Republic Indonesia (PRRI). In addition, formulation and limitation of problem that the background of the case building BPPI? And what is actioning BPPI in improving independence fenimist at Sumatera Barat generally and especially?The purpose of the research are: 1) Describe data about group activity at Padang in first condition (Augt-Nov) . 2) Try explaining actioning BPPI in developing indepence feminist. This research use history method such as: a) Heuristic, b) Source Critique, c) Analyzing, d) Histography, and e) Written system. Library research and research location that data is got from field and source from book, article,